Migration, Remittances and Socio-Economic Effects of Myanmar Migrant Workers' Families Left Behind - Khin Soe, Kyi (2021)
This study aims to investigate migration, remittances, and socioeconomic effects of Myanmar migration workers’ families left behind in Mon State, Myanmar. A combined quantitative and qualitative approach was used. A survey was conducted on 494 respondents from the left-behind families by using a pre-tested structured questionnaire. In-depth interviews were conducted with 15 informants to explore the experiences of migrant families. It was found that the common reasons for overseas employment were lack of job opportunities, not having enough earnings, and difficulty in finding jobs relevant to education. Thailand is the major destination country, followed by Malaysia and South Korea while the least amount of remittances was sent by the migrants from Thailand. The majority of families used Hundi as their main remittance transaction channel. After migration, both financial assets and perception on economic indicators improved significantly. Family perception on social indicators has significantly become better; however psychological problems are found to be worse off after migration. It can be concluded that international labour migration has economically and socially benefited to the migrant families; however psychologically detrimental to a large extent. The narratives of informants produced three themes ̶ migration as conventional choice; migration as misery; and migration as success. Labour migration is a major livelihood of the families and provides positive financial and economic effects, making them to assume migration works as success. Negative psychosocial consequences to left-behind spouses, elderly, and children in the families pushing them to assume migration works as misery. With the two strands of migration effects, engaging in safe migration practices and arranging social welfare and protection policies for migrants and their left-behind families are major challenges faced by Myanmar. In addition, creating local employment opportunities of young and working age people and preparing them for job relevant skills through technical vocational education training are priority areas to be focused on to escape from migration trap